Thermal characterization of phase‐changing materials as stabilized thermal energy storage materials in impregnated wood. Issue 1 (14th August 2022) - Can, Ahmet
Abstract: In this study, a palmitic acid‐shellac (PA/Sh) mixture was impregnated into spruce wood. Subsequently, the properties of the modified wood were investigated by thermal gravimetric analysis, differential scanning calorimetry, Fourier‐transform infrared (FT‐IR) spectroscopy, and scanning electron microscopy (SEM). After the impregnation, 10% to 25% weight gains were obtained in the samples. The FT‐IR result demonstrated the physical composition of the PA/Sh mixture. The modified wood samples PA, PASh2, and PASh3 had phase transition temperatures of 59.33°C, 58.37°C, and 58.76°C, and high‐latent heat of 27.54, 10.73, and 14.73 J/g, respectively. The modified wood exhibited high thermal stability because the working temperature was much lower than the decomposition temperature. The SEM analysis showed that the wood microscale pores were filled with PA/Sh. The results obtained determined that the property of storing and releasing solar thermal energy of the modified wood rendered it suitable for practical applications. Abstract :